التزاحم بين البائع المحتفظ بالملكية ودائني المشتري - اللهيبي صالح احمد (Journal of Legal Sciences, 2017)
Handling search partial very important, a contention seller if I keep property under the condition with the creditors of the buyer, since it is known that the creditors of the buyer deal with the buyer as the owner did not know anything about this condition, and thus the UAE legislator in Article 732 of the UAE Commercial Transactions Law No. 18 for the year 1993 came by virtue of a lack of protest provided to retain ownership in the face of a group of creditors - creditors of the buyer - and the goods had entered the stores, on the other hand civil transactions law No. 5 of 1985 ratedid not want anything about it in the, and therefore, the seller would be affected obvious damage it came this study-in-law civil attempt to reach the protection seller that we find the first of the buyer’s creditors in the legal protection, but in order to prevent collusion terms .